The role of vitamin D in the human body and the influence of vitamin D on the proliferation of cancer cells - Dudzińska, Wioleta; Chilińska, Oliwia; Warias, Paulina; Maskiewicz, Paulina; Maniak, Eliza; Strońska, Aleksandra (Journal of Education, Health and Sport, 2021)
The publication focuses on the presentation of the role of vitamin D3 in the human body. The content contains important information on the influence of vitamin D3 on the course of Covid-19 disease caused by the Sars-Cov-19 virus. Cholecalciferol has been studied for years. Its basic functions include the regulation of bone mineral metabolism and calcium-phosphorus metabolism. In addition, the publication characterizes the course of vitamin D3 synthesis and presents the important role of vitamin D3 in the body. Additionally, the currently conducted research in terms of anti-cancer properties of selected vitamin D3 analogues was described.